The Influence of Macroeconomics Policy to Indonesia Banking Sector Performance - Seflizon Seflizon (Universitas Trisakti, 2007)
The Indonesia monetary crisis in mid 1997 was the background of this research. The objective of this research is to identify the influence of macroeconomics policy to end the monetary crisis and restructuring credibility of banking institution. This research uses testing hypotheses on nonparametric statistics. The data analysis used macroeconomics policy in fiscal, monetary, balance of payment, and influence toward controlling of monetary crisis on foreign exchange and credibility banking institution as indicator of bank performance. The data was devided into two periods, 1997-2001 and post crisis period 2002-2006. The result showed that: monetary crisis does not always refer to foreign exchange is not significant. It is true that monetary crisis is banking institution crisis in all aspect whether management and financial, and banking indicator showed better performance significantly compared to post crisis and long crisis.